Fluid geochemistry of Lessini Mountain's thermal area: New data from Caldiero, S. Ambrogio-Colà di Lazise and Sirmione hydrothermal districts (Verona-Brescia Provinces, Italy). (May 2022) - Lelli, M.; Agostini, L.; Monegato, G.; Cavazzini, G.; Fasson, A.; Giaretta, A.; Galgaro, A.; Doveri, M.
Highlights: New chemical and isotopic characterization of Lessian's thermal districts is provided. The hydrogeochemistry approach used identify main active physico-chemical processes. New geothermometric estimations for the studied thermal waters are carried out. The depths reached by thermal waters are estimated by geochemical data elaboration. The geochemical model agree with evidences from geological and structural data. Abstract: The Po Plain, located in northern Italy between the Alps and the Apennines, hosts several thermal water spots. Some of these thermal waters belong to the thermal districts of Brescia and Verona provinces. This thermalism has been used for therapeutical purposes since the "Roman Age". During Sept. 2014 - Aug. 2015, a detailed sampling program was carried out to collect water samples of thermal and cold waters in the Lessini Mountain's thermal area, including those in the Sirmione thermal district (project area). Assessment of water chemistry and isotope data, identified distinctive characteristics of thermal waters belonging to the thermal districts investigated in this project (i.e. Caldiero, S.Ambrogio Valpolicella, Colà di Lazise, Lazise and Sirmione). In particular, data show that the Sirmione thermal waters are characterized by a higher temperature and a total salinity and by chemical and isotopic fingerprints that are distinct and unrelated to those of other thermal waters. On the other hand, the data indicate potential correlations between samples from S.Ambrogio Valpolicella and Colà di Lazise and local cold water. Geochemical modeling conducted using PHREEQC, showed that a mixing accompanied by calcite precipitation can explain the chemical characteristics observed in the thermal waters and some cold springs assessed in this project. New geothermometric estimations were performed for main thermal components, obtaining temperature ranges (in°C) of about 92–99, 67–74 and 51–58, respectively for Sirmione, S.Ambrogio Valpolicella-Colà di Lazise and Caldiero thermal districts. Temperature ranges obtained in this work were used to gain an insight into the possible depth reached by thermal waters in the project area, which is characterized by the normal geothermal gradient (30°C/Km). Finally, geochemical findings were elaborated and integrated with geological and structural data in a proposed conceptual model of water circulation. The agreement within data sets is satisfactory in particular in relation to the depth of carbonate-evaporite formations, which represent the thermal reservoirs. Infiltrating waters can seep into the deep through fractured rocks, reaching the Carnian to Upper Cretaceous carbonates and evaporites. In the Caldiero thermal districts the depth reached by thermal waters coincides with the level of the Carnian evaporites (≈ 1.3–1.6 Km) and it agrees with the important role played by dissolved sulphates evidenced by geochemical data. Thermal fluids in Sirmione and S. Ambrogio Valpolicella – Colà di Lazise thermal districts likely interact with Permian-Middle Triassic formations, which are located at greater depths (≈ 2.7–3 Km and ≈ 1.9–2.1 Km, respectively). Once heated at depth, thermal fluids rise through main faults and/or thrust faults, where they may be diluted by circulating surface cold waters.